2008
DOI: 10.4314/gjass.v7i1.2365
|View full text |Cite
|
Sign up to set email alerts
|

Genetic And Environmental Factors Affecting Growth Traits Of Goats In Semi Arid Area Of Nigeria

Abstract: BSTRACT Growth performance of 194 kids of Sahel (S), Red Sokoto (RS) and West African Dwarf (WAD) breeds of goats from birth to 9 months of age was studied. Effect of breed was significant (p<0.001) with S (2.07kg-13.49kg) breed being heavier than RS (1.81kg-13.77kg) and WAD (1.42KG-8.63 kg) though they were comparable with RS at 9months. At all ages, WAD was the lightest. Seasonal effect showed that animals born in the wet season were significantly (p<0.001) heavier than those born in the dry season at the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The results of analysis of variance in Table (2) show that fixed effects on the studied traits were generally significant (P<0.01or P<0.05), except for the effect of parity on WW and ADG of Baladi kids which were not significant. The results found in this study are in agreement with those reported by Alade et al 2008, Boujenane and El Hazzab 2008, Otuma and Osakwe 2008, Rashidi et al 2008, Hermiz et al 2009, Zhang et al 2009, Thiruvenkadan et al 2009, Sodiq et al 2010, Supakorn et al 2011, Mohammadi et al 2012, Andries 2013, Bedhane et al 2013, Deribe and Taye 2013, Kuthu et al 2013, Osman 2013, Bingol et al 2014, Ray et al 2015, Gupta et al 2016, Syahirah et al 2016, Bolacali et al 2017, Msalya et al 2017, and Rout et al 2018.…”
Section: I-fixed Effectssupporting
confidence: 91%
“…The results of analysis of variance in Table (2) show that fixed effects on the studied traits were generally significant (P<0.01or P<0.05), except for the effect of parity on WW and ADG of Baladi kids which were not significant. The results found in this study are in agreement with those reported by Alade et al 2008, Boujenane and El Hazzab 2008, Otuma and Osakwe 2008, Rashidi et al 2008, Hermiz et al 2009, Zhang et al 2009, Thiruvenkadan et al 2009, Sodiq et al 2010, Supakorn et al 2011, Mohammadi et al 2012, Andries 2013, Bedhane et al 2013, Deribe and Taye 2013, Kuthu et al 2013, Osman 2013, Bingol et al 2014, Ray et al 2015, Gupta et al 2016, Syahirah et al 2016, Bolacali et al 2017, Msalya et al 2017, and Rout et al 2018.…”
Section: I-fixed Effectssupporting
confidence: 91%